EVALUATION OF THE IMPLEMENTATION OF A REFERRAL SYSTEM IN THE COMMUNITY HEALTH CENTER OF ABELI, KENDARI, INDONESIA - Risky, Sartini; Nofitasari, Ari (Public Health of Indonesia, 2017)
Background: The referral rate in Southeast Sulawesi in the first-level health facilities was still high, which reached 17% in 2016. Ideally, the maximum referral rate in the first-level facilities should be no more 5%.  Objective: This study aims to evaluate the implementation of the first-level referral system in terms of availability of health personnel, facilities and medicines, and understanding of health officers on the referral system at the Community Health Center of Abeli.Methods: In-depth interviews were conducted with a total of 5 health facility managers. All the materials were analyzed using a qualitative thematic analysis approach.Results: Three themes emerged from data; namely human resources (Lack of responsibility of midwives, Lack of communication between staffs, Lack of the number of physician, Understanding of health personnel regarding referral system), availability of facilities, and availability of drugs.Conclusion: Availability of human resources, facilities and drugs is unreliable. Effort should be made to ensure the quality of service provided. This should imply, amongst other things, that human resources, drugs and facilities are adequately available and accessible.